Chemical and technological composition of spring green pea (Pisum sativum var. hortense L.) genotypes - Červenski, Janko; Zec, Srđan; Kiprovski, Biljana; Danojević, Dario; Tamindžić, Gordana; Ignjatov, Maja; Miljaković, Dragana (Journal of Agricultural Sciences (Belgrade), 2024)
Through the chemical-technological analysis of (technologically) mature spring pea genotypes, we examined the following traits: moisture content, ash, oil, total nitrogen, protein, total sugars, starch, cellulose and content of total soluble solids (Brix) (eight lines and two varieties). This research aimed to determine the chemical and technological characteristics of the selected spring pea genotypes, assess the variability structure of pea genotype characteristics, and therefore assess the contribution of individual characteristics to the overall variability. Lines with a higher protein content SK-1, SK-5 and SK-10 as well as lines with a higher sugar content SK-4, SK-5 and SK-8, which will be included in the development of pea varieties, will have a special value in the selection of high protein and high sugar vegetable peas. Pea genotypes SK-6, SK-7 and SK-8 with a higher Brix can be used in the earlier selection of sweeter peas suitable for fresh or early spring consumption. Based on the cluster analysis, the pea genotypes were grouped into individual groups to assess the impact on the variability of each trait. By principal component analysis, the four separate components cumulatively explained 91.91% of the total variability.